ANALISIS PENGARUH FRAUD DIAMOND DAN FEE AUDIT TERHADAP PENGUNGKAPAN ATAS KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Imanuel Yoka Prasetia; Totok Dewayanto (Diponegoro Journal of Accounting, 2021)
The purpose of this research was to determine the effect of elements of fraud diamond (pressure, opportunity, rationalization, capability) and audit fees on the disclosure of fraudulent financial statements, in manufacturing companies listed on the Indonesia Stock Exchange.The population in this study consisted of all manufacturing companies on the Indonesia Stock Exchange for the 2017-2019 period. Sampling was done by using purposive sampling method. The total sample of this research is 71 companies.This research uses multiple regression analysis for hypothesis testing. The results of this research indicate that pressure and opportunities have a positive and significant effect on financial statement fraud. Meanwhile, rationalization, capability, and audit fees have no effect on fraudulent financial statements.